2007
DOI: 10.1111/j.1365-313x.2007.03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Not all ALMT1‐type transporters mediate aluminum‐activated organic acid responses: the case of ZmALMT1 – an anion‐selective transporter

Abstract: SummaryThe phytotoxic effects of aluminum (Al) on root systems of crop plants constitute a major agricultural problem in many areas of the world. Root exudation of Al-chelating molecules such as low-molecular-weight organic acids has been shown to be an important mechanism of plant Al tolerance/resistance. Differences observed in the physiology and electrophysiology of root function for two maize genotypes with contrasting Al tolerance revealed an association between rates of Al-activated root organic acid rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 44 publications
5
102
0
Order By: Relevance
“…In contrast, ZmALMT1 (Piñeros et al, 2008) and ZmALMT2 (Ligaba et al, 2012), two members in the ALMT family, were not found to be associated with maize Al tolerance.…”
Section: The Almt Familymentioning
confidence: 68%
“…In contrast, ZmALMT1 (Piñeros et al, 2008) and ZmALMT2 (Ligaba et al, 2012), two members in the ALMT family, were not found to be associated with maize Al tolerance.…”
Section: The Almt Familymentioning
confidence: 68%
“…similarly relies on the ALMT transporter Ma1 which mediates malate accumulation into the vacuoles of developing fruit cells [14]. In maize (Zea mays L.), ZmALMT1 and ZmALMT2 are mainly expressed in root tissues and likely function to assist in balancing charges during nutrient uptake [12,13]. Both proteins localise to the plasma membrane and both are permeable to inorganic anions but ZmALMT2 is also permeable to organic anions as demonstrated by the constitutive release of malate from the roots of transgenic Arabidopsis plants expressing ZmALMT2 [13].…”
Section: Almt Genes Perform Various Functions Among Plantsmentioning
confidence: 99%
“…The characterised ALMT members show a range of functions including Al resistance [1][2][3][4], stomatal function [5][6][7][8][9][10][11], mineral nutrition [12,13,39], microbe interactions [16,17], fruit acidity [14,15], and seed development [18]. Members which have been characterised are widely distributed in higher plant families of Poaceae, Brassicaceae, Fabaceae, Rutaceae, Rosaceae, Vitaceae and Solanaceas (Table 1).…”
Section: Almts Are Widely Distributed In the Genomes Of Higher Plantsmentioning
confidence: 99%
See 2 more Smart Citations